PERANAN TOTAL QUALITY MANAGEMENT (TQM) DI SEKOLAH DASAR - Dewi, Putu Yulia Angga; Primayana, Kadek Hengki (Jurnal Penjaminan Mutu, 2019)
Management of education by creating a conducive learning environment and successfully fulfilling commitments in fulfilling promises as educational leaders. The low quality of human resources is a fundamental problem that can hamper development and national economic development. Along with the advancement of knowledge and technology, the socio-cultural life, socio-economy is increasingly unacceptable to space and time. In order to build the quality of Indonesian people who are able to challenge it, clearly it requires human resources that can be relied upon in the face of competition. TQM is a quality management system that is related to continuous improvement in improving the quality of education from various aspects of sustainability. Educational quality that is acceptable from customer needs and satisfaction. The application of TQM in school organizations is carried out as an effort to improve the quality of education in schools, thereby improving the quality of schools by improving the quality of education of high quality. The implementation of a management system is always disrupted by balance. Two parties who are pro and contra arise, accept TQM and reject TQM. TQM's refusal because it affects changes in management, namely changing established values. With this pillar, it is expected to be able to help schools improve their educational processes. The implementation of integrated Quality Management in schools is inseparable from the efforts of the principal to provide assistance to the school.